Efficacy of Combination of Meropenem with Gentamicin, and Amikacin against Resistant E. coli Isolated from Patients with UTIs: in vitro Study - Maysaa A. abdul khaleq; Abdulkareem H. Abd; Maysaa A. dhahi (College of Pharmacy University of Baghdad, 2017)
Seventy five E. coli isolates were collected from urine of patients with urinary tract infections in AL-Kadhimia and AL-Yarmook teaching hospitals in Baghdad for a period between 22/11/2009 to 15/3/2010,  from these samples twenty five isolates were selected according to their pattern of the highest resistance as these showing multi-drug resistances and tested to specify their minimum inhibitory concentration for (meropenem, gentamicin and amikacin), meropenem was found having the lowest MIC comparing with others. This study also includes in vitro effects of various combinations of three types of antimicrobials (meropenem, gentamicin and amikacin) against twenty five E. coli isolates.Among combinations the combination of meropenem with the other types of antimicrobials showed high synergistic effect when 1/4+1/4 MIC for each antimicrobial were used. While combinations of amikacin with gentamicin in some isolates showed additive effect when 1/2+1/2 MIC for each antimicrobial were used. The plasmid profile for the twenty five E. coli isolates were studied using Pure Yeild ™ plasmid Miniprep system- Cat.# A1220 - Promega- USA. In order to determined the presence of plasmid for antimicrobials resistance.